2017
DOI: 10.1037/tra0000216
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in Hispanic youth with psychiatric symptoms: Investigating gender and family effects.

Abstract: Objective Hispanic youth in the general community experience traumatic events and display symptoms of psychological distress more frequently than Caucasian youth. However, little is known about how traumatic experiences in this ethnic minority population relate to psychopathology in clinical samples and whether these outcomes vary by gender and are impacted by family functioning. We hypothesized that traumatic stress reactions, including PTSD, internalizing and externalizing symptoms would vary by gender and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Although hypervigilance and gender were not correlated in bivariate analyses, they were partially correlated when controlling for age, nationality, trauma, family resilience, and discrimination. These findings line up with other studies concluding that adolescent girls in general (McLaughlin et al, 2013) and Latina girls in particular (Suarez-Morales et al, 2017) are at greater risk for developing PTSD symptoms, potentially related to their underlying neurobiology (Garza & Jovanovic, 2017) and gender role socialization (Street & Dardis, 2018). Gender role socialization may contribute to girls’ and women’s schemas, for example, about self-blame, responsibility, and world as dangerous, that exacerbate PTSD symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Although hypervigilance and gender were not correlated in bivariate analyses, they were partially correlated when controlling for age, nationality, trauma, family resilience, and discrimination. These findings line up with other studies concluding that adolescent girls in general (McLaughlin et al, 2013) and Latina girls in particular (Suarez-Morales et al, 2017) are at greater risk for developing PTSD symptoms, potentially related to their underlying neurobiology (Garza & Jovanovic, 2017) and gender role socialization (Street & Dardis, 2018). Gender role socialization may contribute to girls’ and women’s schemas, for example, about self-blame, responsibility, and world as dangerous, that exacerbate PTSD symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to Non‐Hispanic Whites, Latinx adults report a rising burden of depressive symptoms (McKnight‐Eily et al., 2021; Ward et al., 2019). Similarly, Latinx youth experience higher rates of suicide, post‐traumatic stress disorder, and substance use compared to their non‐Hispanic peers (Suarez‐Morales et al., 2017; Taylor & Ruiz, 2017; Vargas et al., 2021). Rates of mental health difficulties are thus rising in the Latinx community, particularly as the number of years living in the United States and exposure to new acculturative stressors increases (Perreira et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In another study of Hispanic families, family conflict more strongly predicted boys’ depressive symptoms than girls (Lorenzo-Blanco et al, 2012). Similarly, high family conflict has been linked to Hispanic boys’ post traumatic stress disorder symptoms but not girls’, whereas family cohesion was more strongly linked to Hispanic girls’ post traumatic stress disorder symptoms than boys’ symptoms (Suarez-Morales et al, 2017). Another study of Mexican immigrant families found that the link between adolescent–parent relationships and adolescent psychological adjustment was stronger for girls than boys (Updegraff et al, 2009).…”
Section: Internalizing Symptoms Among Hispanic Adolescentsmentioning
confidence: 99%